Elevated Serum TNF-α Is Related to Obesity in Type 2 Diabetes Mellitus and Is Associated with Glycemic Control and Insulin Resistance. (31st January 2020) - Alzamil, Hana
Abstract : Background . Diabetes and obesity are very common associated metabolic disorders that are linked to chronic inflammation. Leptin is one of the important adipokines released from adipocytes, and its level increases with increasing body mass index (BMI). Tumor necrosis factor alpha (TNF- α ) is a cytokine that is released by adipocytes and inflammatory cells in response to chronic inflammation. Type 2 diabetes mellitus (T2DM) is believed to be associated with low-grade chronic inflammation. The current study aims to investigate the involvement of leptin and TNF- α in T2DM associated with obesity. Methodology . This is a cross-sectional study involving 63 healthy volunteers and 65 patients with T2DM. Body composition was measured, and fasting venous blood samples were analyzed for blood glucose, glycosylated hemoglobin (HbA1c), basal insulin, leptin, and TNF- α . HbA1c was measured by the affinity column method. Insulin, leptin, and TNF- α immunoassays were performed by the ELISA technique. Insulin resistance and beta-cell function were assessed using the homeostasis model assessment (HOMA-IR and HOMA-B). Results . Our study showed a significantly higher level of TNF- α in T2DM patients compared to controls (7.51 ± 2.48 and 6.19 ± 3.01, respectively; p = 0.008 ). In obese diabetic patients, the serum level of TNF- α was significantly higher in comparison with nonobese diabetic patients (p < 0.018 ) and obese nondiabetic group (p < 0.001 ). TNF- α correlated positively with HbA1c ( r = 0.361, p = 0.003 ) and HOMA-IR ( r = 0.296, p = 0.017 ) in patients with T2DM. Conclusion . TNF- α is associated with concurrent obesity and T2DM and correlates with HbA1c. This suggests that TNF- α needs further investigation to explore if it has a role in monitoring the effectiveness of management in individuals with obesity and T2DM.